Influence of Benign/Malicious Envy on Mobile Phone Addiction: Mediating Role of Loneliness and Self-Control. - Zhang, Mengmeng; Xiang, Yanhui (International Journal of Mental Health & Addiction, 2023)
It has become a significant issue that an increasing number of adolescents are addicted to mobile phones. From the perspective of social comparison theory, this study aims to explore the relationship between benign envy/malicious envy and mobile phone addiction, as well as the role of loneliness and self-control in it. A total of 1951 valid samples were collected from primary and middle schools in China. The research showed that benign envy (malicious envy) could negatively (positively) predict mobile phone addiction. Meanwhile, self-control played as a mediator between benign envy/malicious envy and mobile phone addiction, while loneliness had no significant mediating effect. In addition, benign envy/malicious envy influenced mobile phone addiction by the chain mediation of "loneliness → self-control." For the first time, this study reveals the effects of benign envy and malicious envy on mobile phone addiction and the internal mechanisms from the perspective of social comparison theory, offering illuminations for the prevention of mobile phone addiction.